2007
DOI: 10.1158/0008-5472.can-07-0444
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Signaling in Prostate Stromal Cells Supports Prostate Carcinoma Growth by Up-regulating Stromal Genes Related to Tissue Remodeling

Abstract: Increasing evidence points to an active stromal involvement in cancer initiation and progression. Cytokines derived from tumor cells are believed to modulate stromal cells to produce growth and angiogenic factors, which in turn provide the tumor with the necessary microenvironment for expansion and invasion. Transforming growth factor B (TGFB) has been implicated as a candidate cytokine to mediate this communication. However, how its signaling in stromal cells regulates tumorigenesis and tumor progression rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 45 publications
(57 reference statements)
4
54
0
Order By: Relevance
“…As an in vivo experimental model, several groups have demonstrated that coinoculation of commercialized human prostatic stromal cells (PrSC) with human PCa cells increased tumorigenicity in terms of tumor incidence and tumor growth (Uemura et al 2005, Verona et al 2007). In addition, Kawada et al (2006) have shown that the PrSC-conditioned medium increased the cell proliferation of human PCa cells in vitro, suggesting that the secreted factors from PrSC-regulated tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As an in vivo experimental model, several groups have demonstrated that coinoculation of commercialized human prostatic stromal cells (PrSC) with human PCa cells increased tumorigenicity in terms of tumor incidence and tumor growth (Uemura et al 2005, Verona et al 2007). In addition, Kawada et al (2006) have shown that the PrSC-conditioned medium increased the cell proliferation of human PCa cells in vitro, suggesting that the secreted factors from PrSC-regulated tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This stromal reaction is an early feature common to many malignant epithelial neoplasms initiated via the action of cancer cell-derived secreted factors, in particular transforming growth factor b1, that modify the surrounding stroma generating a microenvironment which in turn further supports tumor growth and progression (Barclay et al 2005, Ao et al 2007, Verona et al 2007, Sampson et al 2011. The tumorassociated 'reactive' stroma is characterized in particular by activation of fibroblasts but also by recruitment of inflammatory cells, ECM remodeling and enhanced angiogenesis.…”
Section: Benign and Carcinoma-associated Prostate Stromal Cellsmentioning
confidence: 99%
“…The normal prostate has an abundance of stromal components, mainly well-differentiated smooth muscle cells. In prostate tumors, however, fibroblasts surrounding cancer cells are associated not only with the initiation of cancer cells but also with tumor growth and progression to androgen independence (11)(12)(13). Olumi et al demonstrated stroma-induced malignant transformation, indicating that fibroblasts surrounding epithelia play an important role in PCa development (14).…”
Section: Introductionmentioning
confidence: 99%
“…Olumi et al demonstrated stroma-induced malignant transformation, indicating that fibroblasts surrounding epithelia play an important role in PCa development (14). Other groups reported that coinoculation of PCa cells with fibroblasts increased tumorigenicity and implied the promotion of angiogenesis (11,15,16). Therefore, the inhibition of tumor-stroma interactions with addition of the suppression of cancer cell growth might lead to synergistic effects on tumor control.…”
Section: Introductionmentioning
confidence: 99%